Biological Effects of Hydrogen Water on Subjects with NAFLD: A Randomized, Placebo-Controlled Trial - Branislav Kura; Maria Szantova; Tyler W. LeBaron; Viliam Mojto; Miroslav Barancik; Barbara Szeiffova Bacova; Barbora Kalocayova; Matus Sykora; Ludmila Okruhlicova; Narcisa Tribulova; Anna Gvozdjakova; Zuzana Sumbalova; et al. (MDPI AG, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a liver pathology affecting around 25% of the population worldwide. Excess oxidative stress, inflammation and aberrant cellular signaling can lead to this hepatic dysfunction and eventual carcinoma. Molecular hydrogen has been recognized for its selective antioxidant properties and ability to attenuate inflammation and regulate cellular function. We administered hydrogen-rich water (HRW) to 30 subjects with NAFLD in a randomized, double-blinded, placebo-controlled manner for eight weeks. Phenotypically, we observed beneficial trends (p > 0.05) in decreased weight (≈1 kg) and body mass index in the HRW group. HRW was well-tolerated, with no significant changes in liver enzymes and a trend of improved lipid profile and reduced lactate dehydrogenase levels. HRW tended to non-significantly decrease levels of nuclear factor kappa B, heat shock protein 70 and matrix metalloproteinase-9. Interestingly, there was a mild, albeit non-significant, tendency of increased levels of 8-hydroxy-2'-deoxyguanosine and malondialdehyde in the HRW group. This mild increase may be indicative of the hormetic effects of molecular hydrogen that occurred prior to the significant clinical improvements reported in previous longer-term studies. The favorable trends in this study in conjunction with previous animal and clinical findings suggest that HRW may serve as an important adjuvant therapy for promoting and maintaining optimal health and wellness. Longer term studies focused on prevention, maintenance, or treatment of NAFLD and early stages of NASH are warranted.